PENGARUH KECUKUPAN MODAL DAN KOMPETISI TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Dessy Mauliza; Rulfah M. Daud (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This study is conducted to analyze the influence of capital  adequacy and competition against sharia banks’ profitability. This study applied census method , where study’s population was all sharia bank enlisted in Bank of Indonesia within 2013 until 2015 period. Data used in this study were secondary data.Results of this study show that capital  adequacy and competition together influenced sharia banks’ profitability. Partially, capital  adequacy had negative influence against banks’ profitability while competition had positive influence against sharia banks’ profitability. Keywords— Capital Adequacy Ratio, Competition, Profitability (ROA).